The Fertility Effect of Laws Granting Undocumented Migrants Access to Driving Licenses in the United States - Christian Gunadi (Global Labor Organization (GLO), 2022)
As of 2021, 16 U.S. States and the District of Columbia have implemented laws allowing undocumented migrants to acquire a driver's license. In this paper, I hypothesize that lower barriers to work caused by the ability to obtain driving licenses can affect undocumented migrants' fertility decisions. Using a differencein- differences strategy based on temporal and geographical variation in the implementation of laws granting undocumented migrants access to driving licenses across U.S. states, I find that these laws were associated with about 9% decline in childbirth among likely undocumented married women. Exploring the mechanism, the results of the analysis indicate that granting undocumented migrants access to driving licenses increased the propensity to work along the intensive margin. Among those at work, their usual weekly hours rose by approximately 1.5%.
Keywords: J13; I38; J15; K37; 330; driving licenses; undocumented immigrants; fertility; labor market impacts